2021
DOI: 10.1080/21655979.2021.2008638
|View full text |Cite
|
Sign up to set email alerts
|

MiR-191-5p alleviates microglial cell injury by targeting Map3k12 (mitogen-activated protein kinase kinase kinase 12) to inhibit the MAPK (mitogen-activated protein kinase) signaling pathway in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disease. Multiple reports have elucidated that microRNAs are promising biomarkers for AD diagnosis and treatment. Herein, the effect of miR-191-5p on microglial cell injury and the underlying mechanism were explored. APP/PS1 transgenic mice were utilized to establish mouse model of AD. Amyloid-β protein 1–42 (Aβ1-42)-treated microglia were applied to establish in vitro cell model of AD. MiR-191-5p expression in hippocampus and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Results obtained in animal studies showed that AT-MSC-Exos prevented apoptotic cell death and attenuated ongoing inflammation in neural and retinal tissues (Table 2) [20][21][22][23][24][25][26][27]38,42,53,57,58]. AT-MSC-Exos play a crucially important role in the regulation of intercellular communication of injured parenchymal cells, immune cells, and ECs in the inflamed neural, corneal and retinal tissues [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results obtained in animal studies showed that AT-MSC-Exos prevented apoptotic cell death and attenuated ongoing inflammation in neural and retinal tissues (Table 2) [20][21][22][23][24][25][26][27]38,42,53,57,58]. AT-MSC-Exos play a crucially important role in the regulation of intercellular communication of injured parenchymal cells, immune cells, and ECs in the inflamed neural, corneal and retinal tissues [19].…”
Section: Discussionmentioning
confidence: 99%
“…As determined by transcriptome and multi-omics sequencing technologies, AT-MSC-Exos are enriched with bioactive molecules (microRNAs (miRNAs), enzymes, cytokines, chemokines, immunoregulatory, trophic, and growth factors), that are responsible for AT-MSC-Exo-dependent beneficial effects in inflamed and injured neural and retinal tissues (Table 1) [20][21][22][23][24][25][26][27].…”
Section: Molecular Mechanisms Responsible For the Beneficial Effects ...mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Pairing to the seed region is important for functional binding specificity, and miR-191-5p recognizes canonical target sites by base-pairing in the 3′UTR of human DAPK1. In addition to DAPK1, miR-191-5p has been found to target oxidative stress responsive 1 (OXSR1), 57 special AT-rich binding protein 1 (SATB1), 58 CCAAT-box/enhancer binding protein β (C/EBPβ), 59 mitogen-activated protein kinase kinase kinase 12 (Map3k12), 60 and tripartite motif-containing 14 (TRIM14). 61 These targets have similar sequences that bind to the short seed sequences at the 5′ ends (nucleotides 2−8) of miR-191-5p.…”
Section: ■ Discussionmentioning
confidence: 99%
“…MAPKs are serine-threonine kinases in eukaryotes that mediate a wide variety of intracellular processes, including cell proliferation, differentiation, survival, death, and transformation [ 49 ]. Furthermore, the MAPK pathway is involved in the pathogenesis of AD through multiple downstream signaling pathways, including the induction of neuronal apoptosis [ 50 ]. The above findings indicate that ZNC may ameliorate AD by regulating TCR, TNF, and the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%